Transgression in contemporary media culture. (January 2021) - Hermes, Joke; Hill, Annette
This is the introduction to a special issue on media and transgression, one of early cultural studies' key terms. It inquires into the uses of transgression as a critical concept to query contemporary media culture which is discussed in six case studies: on political satire, Mukbang, cult drama, the policing of film piracy, media scandals, and online trolls. Transgression points to the energy that fuels the media ecology – from content and content production to audience practices and the policing of content ownership. It is the (conscious) overstepping of moral and legal boundaries, that challenges written and unwritten rules. The frisson of rule breaking and the reward of rule re-establishment (whether by powerful parties or everyday gossip) are transgression's bookends. Together they support the cyclical rhythm of media culture that maintains not just our interest as viewers but our interests and connectedness as citizens, whether in celebration, outrage or condemnation.